Effective Communication in Special Education Student Teaching - Graham, Lesley P. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
A panel of student teachers reviewed information on perceived student teaching needs prior to and following special education student teaching experiences, focusing on needs regarding communication with the cooperating teacher. The panel created several lists of positive verbal and written supports for the special education student teacher. Uses of nonverbal communication were also reviewed. Four general techniques for enhancing the relationship between the student teacher and the cooperating teacher were identified: (1) quality time with the cooperating teacher; (2) a system of effective dialogue; (3) a change of self in the student teaching role; and (4) becoming aware of others with consideration of their needs. Lists of suggested positive words and phrases are attached. (DB)
ERIC Note: Paper presented at the Annual International Convention of the Council for Exceptional Children (73rd, Indianapolis, IN, April 5-9, 1995).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Skills; Cooperating Teachers; Disabilities; Elementary School Teachers; Elementary Secondary Education; Higher Education; Interpersonal Communication; Interprofessional Relationship; Preservice Teacher Education; Secondary School Teachers; Special Education Teachers; Student Attitudes; Student Needs; Student Teachers; Teacher Supervision; Speeches/Meeting Papers; Opinion Papers